Drought responses and phenotypic plasticity of maprounea guianensis populations in humid and dry tropical forests - Dos Santos, Marília Grazielly Mendes; Dos Santos Sousa, Alexsandro; Neves, Sâmia Paula Santos; Rossatto, Davi Rodrigo [UNESP]; De Miranda, Lia D'Afonsêca Pedreira; Funch, Ligia Silveira (FapUNIFESP (SciELO), 2021)
The wide distribution of Maprounea guianensis populations in contrasting environments (dry and humid forests) in the Chapada Diamantina, northeastern Brazil, can indicate the phenotypic plasticity of this species in relation to seasonal rainfall, drought regimes, and soil characteristics at different sites. Functional traits were measured in five individuals in each vegetation types. Water potential, succulence, thickness and density leaf, were evaluated during the dry and rainy periods; wood density and the saturated water content of the wood were evaluated in rainy period. Rainfall was monitored monthly for two years. The functional traits and the phenotypic plasticity indices (PPI) were submitted to analysis of variance. Our results demonstrated seasonal and spatial variations in plant functional traits. We found a low capacity for storing water in leaves and woody tissues, associated with soil properties and the seasonal rainfall/drought regimes, conditioning water potential variations that were greatest during the rainy season. Local environmental parameters influenced variations in the functional traits of M. guianensis populations, reflecting phenotypic plasticity. We highlight the connections between drought regimes and plant responses, demonstrating the importance of functional traits associated with water availability (especially water potential). Our study evidences the factors associated with the wide distribution of M. guianensis.
Keywords: Functional traits; Soil properties; Water availability